Preparation and characterization of plasticized poly(lactic acid) with epoxidized palm oil - Selvarajah, V.S. Giita (2012)
Conventional plastics such as polyethylene, polypropylene, and polyethylene terephthalate persist for many years after disposal. They are inappropriate for applications intended for short time such as packaging, which increases the plastic waste disposal. The accumulation of plastic waste in landfills results in long-term environment, economic and waste management problems which need immediate resolution. Rising environmental concerns have directed research to the development of biodegradable polymer materials.